Intraspecific variation in spermoderm pattern of tribe Acacieae (Mimosoideae) using scanning electron microscopy techniques. Issue 2 (21st December 2018) - Alam, Fakhre; Ahmad, Mushtaq; Zafar, Muhammad; Shinwari, Muhammad I.; Luqman, Muhammad; Novruz, Novruzov E.; Sultana, Shazia; Ullah, Farhat; Ahmad, Manzoor
Abstract: Current research carried out in Pakistan is the first report on spermoderm ornamentation of eight species of tribe Acacieae (Mimosoidae) by using scanning electron microscopic techniques representing two genera, Fedherbia and Acacia were examined. Different spermoderm ornamentation were observed, described and discussed for their taxonomic importance. Seeds surfaces of the studied tribe possess novel variations in macro and micro morphology. Great variations were observed in both qualitative and quantitative characters of seeds. Seeds shape was oblong, ovate to elliptical and spermoderm ornamentation was levigate, rugose, polygonal and discoid, colliculate, and papillose type. These variations in the spermoderm ornamentation can be used as an aid in identification and classification of the members of tribe Acacieae. Abstract : In Pakistan it is the first report on spermoderm ornamentation of eight species of tribe Acacieae (Mimosoidae) by using scanning electron microscopic techniques. Great variations were observed in both qualitative and quantitative characters of seeds. These variations in the spermoderm ornamentation can be used as an aid in identification and classification of the members of tribe Acacieae representing two genera Fedherbia and Acacia .